Design Of A Vitiligo Home Phototherapy Using Narrow Band Ultraviolet-B (NB-UVB) Based On Arduino Uno - Atika Hendryani; Hazzie Zati Bayani; Vita Nurdinawati (Politeknik Kesehatan Kemenkes Jakarta II, 2022)
Vitiligo is one of the skin diseases where there is a disorder in skin pigmentation (skin color disorder), which is characterized by the presence of macula hypopigmentation (a condition that causes part of the skin color to become lighter than the surrounding skin color) caused by the loss of melanocyte function (a special cell found under the skin epidermis that functions to produce skin pigments/melanin) chronically and progressively from the epidermis. This disease if left untreated can spread to other parts of the body. Phototherapy is a method to help reduce the spread of spotting on the body by using NB-UVB rays. This therapy should be carried out on an ongoing basis. To reduce contact with others during the Covid-19 pandemic and there is a vitiligo disease therapy protocol, the author designed the Home Phototherapy Vitiligo device. The author made this device by using NB-UVB lamps and HC-SR04 sensors to detect the exposure distance of 3 cm. The radiation dose starts from 150 mJ/cm2 – 3000 mJ/cm2. The author measured the irradiation of the device obtained 2.6 mW/cm2 and then converted to a radiation dose formula to get how long the therapy time was. The therapy time is obtained level 1 (58 seconds) – level 22 (1085 seconds). In this device obtained the accuracy of the therapy time at the 58th second, the 540th second and the 1085th second is 99.99%. For the value of the accuracy of the distance at 1 cm is 99.82%, at a distance of 2 cm is 99.96%, at a distance of 3 cm is 99.33%, at a distance of 5 cm is 99.944%.